Opioid Use Disorder during Antepartum and Postpartum Hospitalizations - Kern-Goldberger, Adina R.; Huang, Yongmei; Polin, Melanie; Siddiq, Zainab; Wright, Jason D.; D'Alton, Mary E.; Friedman, Alexander M. (American Journal of Perinatology, 2019)
Objective This study aimed to evaluate temporal trends in opioid use disorder (OUD) during antepartum and postpartum hospitalizations.Study Design This repeated cross-sectional analysis analyzed data from the National (Nationwide) Inpatient Sample. Women aged 15 to 54 years admitted antepartum or postpartum were identified. The presence of OUD was determined based on a diagnosis of opioid abuse, opioid dependence, or opioid overdose. Temporal trends in OUD were evaluated using the Rao–Scott chi-square test. Temporal trends in opioid overdose were additionally evaluated.Results An estimated 7,336,562 antepartum hospitalizations and 1,063,845 postpartum readmissions were included in this analysis. The presence of an OUD diagnosis during antepartum hospitalizations increased from 0.7% of patients in 1998 to 1999 to 2.9% in 2014 (p < 0.01) and during postpartum hospitalizations increased from 0.8% of patients in 1998 to 1999 to 2.1% of patients in 2014 (p < 0.01). Risk of overdose diagnoses increased significantly for both antepartum hospitalizations, from 22.7 per 100,000 hospitalizations in 1998 to 2000 to 70.3 per 100,000 hospitalizations in 2013 to 2014 (p < 0.001), and postpartum hospitalizations, from 18.8 per 100,000 hospitalizations in 1998 to 2000 to 65.2 per 100,000 hospitalizations in 2013 to 2014 (p = 0.02).Discussion Risk of OUD diagnoses and overdoses increased over the study period for both antepartum and postpartum hospitalizations.
Keywords: opioid use disorder; pregnancy outcomes; opioid overdose; maternal risk